A new molecular surveillance system for leishmaniasis - Pandey, Kishor; Pandey, Basu Dev; Mallik, Arun Kumar; Acharya, Jyoti; Kato, Kentaro; Kaneko, Osamu; Ferreira, Pedro Eduardo (The American journal of tropical medicine and hygiene, 2014)
Presently, global efforts are being made to control and eradicate the deadliest tropical diseases through the improvement of adequate interventions. A critical point for programs to succeed is the prompt and accurate diagnosis in endemic regions. Rapid diagnostic tests (RDTs) are being massively deployed and used to improve diagnosis in tropical countries. In the present report, we evaluated the hypothesis of, after use for diagnosis, the reuse of the Leishmania RDT kit as a DNA source, which can be used downstream as a molecular surveillance and/or quality control tool. As a proof of principle, a polymerase chain reaction-based method was used to detect Leishmania spp. minicircle kinetoplast DNA from leishmaniasis RDT kits. Our results show that Leishmania spp. DNA can be extracted from used RDTs and may constitute an important, reliable, and affordable tool to assist in future leishmaniasis molecular surveillance methods.